The ‘Woke’ way or the highway: American democracy in the age of ‘Wokism’ and ‘Cancel Culture’ - Fon, Nguh Nwei Asanga (Springer Nature, 2024)
This paper explores the emergence and proliferation of Wokism and Cancel culture in the context of democracy. It traces the origins and evolution of the aforementioned concepts and their contemporary application through the conceptual framework of concept appropriation. The key finding is that the current discussions on racism and social justice are significantly dependent in the way concepts like ‘Whiteness’ and ‘Blackness’ are interpreted. This enquiry reveals a tendency to conflate ‘Whiteness’ and ‘White supremacy’ and to appropriate ‘Blackness’ in a way that creates an otherness that distinguishes African-Americans from other members of the Black race. It also identifies the dangers of Wokism and Cancel culture to democracy like impediment to the rule of law and free speech. The major contribution of this paper is the utility of concept appropriation in explaining how ambiguous and benign concepts can be employed to re-characterize racialization and influence the understanding of race relations. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.
Keywords: Blackness; Cancel culture; Democracy; Social justice; Whiteness; Wokism